Trend and Variability Analysis and Forecasting of Wind-Speed in Bangladesh (Journal of Environmental Science and Natural Resources, 2013)
An attempt was made to examine the trend and variability pattern for decadal, annual and seasonal (crop seasons) average prevailing wind-speed (APWS) for six divisional stations in Bangladesh namely Dhaka, Rajshahi, Khulna, Barisal, Sylhet and Chittagong. The monthly APWS (2009-2012) were forecasted using univariate Box-Jenkins modeling techniques on the basis of minimum root mean square forecasting error. The growth rates for annual and seasonal APWS were found to be negative with nonstationary but normal residual for all regions except Barisal and the Prekharif season for Khulna. The rates for Barisal were observed positive with normal and nonstationary residual. The significant positive growth rate for coefficient of variations (CV) of the annual APWS was experienced for Khulna (0.155*) and the less positive rate for Rajshahi (0.011) with nonstationary residual while for others it was established as negative. The findings support that the climate of this country is changing in terms of the APWS.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14801 J. Environ. Sci. & Natural Resources, 5(2): 97-107 2012